2015
DOI: 10.3138/cjccj.2013.e37
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment, GDP, and Crime: The Importance of Multiple Measurements of the Economy

Abstract: Le lien complexe entre le chômage et le crime est formé de deux mécanismes indépendants et antagonistes : l'effet de motivation et l'effet de tutelle/d'opportunité. Cantor et Land (1985), après avoir présenté un modèle synthétisant ces deux effets, ont découvert que l'effet de tutelle/d'opportunité dominait. Des études récentes mettent ces résultats en doute et utilisent le chômage pour mesurer la performance économique. Certaines de ces nouvelles études utilisent une mesure directe de l'économie des États amé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 43 publications
(70 reference statements)
4
35
0
2
Order By: Relevance
“…A pesar de la abundante literatura que pone a prueba la posible relación existente entre el desempleo y la tasa de mortalidad por homicidios, no se ha logrado aún un consenso sobre su efecto 44 . Esto es, investigaciones como la aquí presentada, han encontrado que el desempleo tiene un efecto positivo y significativo sobre las tasas de homicidios y por lo que se pude considerar un predictor importante de la violencia homicida 45,46 . Otras investigaciones, por el contrario, hallan un efecto negativo del desempleo en la tasa de homicidios 47 o que ambas variables son independientes 48 .…”
Section: Discussionunclassified
“…A pesar de la abundante literatura que pone a prueba la posible relación existente entre el desempleo y la tasa de mortalidad por homicidios, no se ha logrado aún un consenso sobre su efecto 44 . Esto es, investigaciones como la aquí presentada, han encontrado que el desempleo tiene un efecto positivo y significativo sobre las tasas de homicidios y por lo que se pude considerar un predictor importante de la violencia homicida 45,46 . Otras investigaciones, por el contrario, hallan un efecto negativo del desempleo en la tasa de homicidios 47 o que ambas variables son independientes 48 .…”
Section: Discussionunclassified
“…Based on previous studies it can be concluded that unemployment is one of the determinants of economic growth, for accelerate the rate of economic growth / GDP it must reduce the unemployment rate. Meanwhile, GDP is an indicator of economic growth that must be increased to achieve sustainable economic development for the welfare of the people of a country (Andresen, 2015;Khumairoh, Aida, Qomariah, & Nasir, 2018;Pratama & Utama, 2019;Sarjono, Anwar, & Darmansyah, 2018;Siti Fatimah, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This represents roughly one-third of the increase in Hispanic arrests identified above. Since crime rates can fluctuate both seasonally and with other economic conditions (Andresen 2015), Table 6 estimates the model on the full sample for all racial/ethnic groups, and introduces controls for the unemployment rate and a time trend. In Column 1, the coefficient for the post-287(g) period is negative and significant, but smaller than that of the baseline model.…”
Section: A Main Resultsmentioning
confidence: 99%